The Implementation of Accountability, Transparency and Internal Control on Budget Performance at the Working Unit of KPPN Bandung II - Fitriani, Laila; Silviana (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2024)
This research aims to investigate how Accountability, Transparency, and internal control affect budget performance in the KPPN Bandung II working unit. This research uses the concept of value for money. The population of this study consists of 187 respondents at KPPN Bandung II, and 147 respondents from this population were taken as samples. Sampling was conducted using the purposive sampling method. The primary data collection method uses a questionnaire. The analysis method used multiple linear regression analysis. The results of this study indicate that transparency does not affect budget performance based on the concept of value for money in the KPPN Bandung II Work Units. This is evidenced by the absence of an official website containing budget disclosures to the public from each Work Unit. Conversely, accountability and internal control significantly positively impact budget performance with the concept of value for money in the KPPN Bandung II Work Units. Lack of transparency hinders effective public oversight. Therefore, it is necessary to improve the reporting system, increase access to budget information, and strengthen monitoring mechanisms. It is recommended to improve the quality of transparency, as well as developing organizational capacity and transparency literacy to support more efficient and effective budget performance.